2015
DOI: 10.1177/1535370215573394
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate protects against cisplatin-induced nephrotoxicity by inhibiting endoplasmic reticulum stress-induced apoptosis

Abstract: Cisplatin (CP)-induced nephrotoxicity hampers its application in clinic. Green tea, particularly its predominant polyphenolic constituent epigallocatechin-3-gallate (EGCG), possesses anti-inflammatory, antioxidant, and anti-apoptotic properties. The present study was designed to investigate the protective effects of EGCG against CP-induced nephrotoxicity in mice. Male C57/BL6 mice in different groups received single injection of CP (20 mg/kg) and EGCG (100 mg/kg) in various sets and kidney tissues and blood we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 42 publications
2
37
1
Order By: Relevance
“…These three polyphenols (i.e. EGCG, QUE and RUT) were reported for their activity in preventing tissue damages from ER stressors such as cisplatin, MPP + , tunicamycin, A23187 and thapsigargin . For example, EGCG was able to prevent cisplatin‐mediated nephrotoxicity .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These three polyphenols (i.e. EGCG, QUE and RUT) were reported for their activity in preventing tissue damages from ER stressors such as cisplatin, MPP + , tunicamycin, A23187 and thapsigargin . For example, EGCG was able to prevent cisplatin‐mediated nephrotoxicity .…”
Section: Discussionmentioning
confidence: 99%
“…EGCG, QUE and RUT) were reported for their activity in preventing tissue damages from ER stressors such as cisplatin, MPP + , tunicamycin, A23187 and thapsigargin. [44][45][46][47] For example, EGCG was able to prevent cisplatin-mediated nephrotoxicity. [44] QUE suppressed ER stress responses in intestinal LS180 and Caco-2 cells exposed to tunicamycin, A23187 and thapsigargin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asaumi et al () demonstrated that EGCG suppressed the activation of pancreatic stellate cells induced by ethanol through the antioxidative effect. Several studies demonstrated that EGCG inhibited ER stress‐induced apoptosis (Wu et al, ; Chen et al, ). However, whether EGCG had effect on the damage of ethanol‐induced β ‐cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…First, the imbalance in ER homeostasis, as multifunctional organelle, caused disturbance of calcium homeostasis, glucose deprivation, increasing of ROS formation and oxidative stress induction [45] . Chen et al showed that EGCG decreased p-ERK, GRP78, caspase-12 of kidney, as ER stress-related markers via inhibition of ER stress-induced apoptosis [46] . Second, a recent study has examined the effect of protection again cisplatin induced renal injury by EGCG through mitochondrial protection by improving mitochondrial electron chain complexes, mitochondrial antioxidant function in enzymes MnSOD and GPX, and improving cisplatin-induced mitochondrial oxidative/nitrative damage and anti-inflammatory effect [37] .…”
Section: Other Related Nephropathymentioning
confidence: 99%